Factors affecting readmission for asthma exacerbation in children attending Alexandria university children-hospital - El-Sayed Eissa, Maged Mohamed; Farouk El Deriny, Ghada Mohamed; Morsy Abo Shaara, Heba Abd Elsalam (International Journal Of Community Medicine And Public Health, 2019)
Background: The admission rate for bronchial asthma has increased dramatically all over the world. This increase in admission influences the children’s quality of life in addition to health care cost. Objective of the study was to identify the risk factors for readmission because of acute asthmatic attacks. Methods: Case control study applied on asthmatic children admitted because of acute asthma attacks attending emergency room, paediatric intensive care unit and inpatient wards of Alexandria university children’s hospital, Alexandria, Egypt in the period from September 2016 to July 2017. The study group was subdivided into 2 groups; group (A) readmitted within one year from first admission and group (B) firstly admitted. Results: The mean age in group (A) and (B) was 9.09±3.98 and 8.65±4.01 respectively. Males were more than females in both groups, and no sex differentiation effects on readmission. The duration of the disease in readmitted group ranged from 1-8 years, it was a risk factor for acute asthma readmission. Viral infection, exercise and dust were risk factors for acute asthma exacerbation readmission. Disease severity was found to have a higher percentage of hospitalization; cases with severe and moderate bronchial asthma compared to mild cases. Readmitted patients had more sleep disturbance and lack of school attendance. Readmitted patients were less adherent to treatment. Conclusions: Duration of the disease, viral infections, common cold, dust and exercise are risk factors for acute asthma readmission. Severity of the disease and adherence to medications affect acute asthma readmission.